Pengaruh Pembelajaran Pemecahan Masalah Terhadap Stres Sekolah Siswa SMK - Suprapti, Suprapti; , Dr. Nanik Prihartanti, M.Si (2014)
The purpose of this study is to figure out the influence of problem solving learning toward level of school stress of vocational school students. Research method of in this paper is using quantitative experimental approach. The selection of subject is conducted by screening using score scale of school stress against 102 students. Subject of the research is 88 students with score category of stress is moderate and high, next from the 88 subjects, randomly it was taken 20 subjects for experimental group and another 20 subjects for controlling group. The result of data analysis toward experimental group subject and controlling group using sample paired t-test it is known that value of t = - 1,535 with 0,144 significant, it means that there are no difference of derivation of school stress between experimental group and controlling group. It can be said that problem solving learning in this research has no effect for the derivation of students' school stress level. Next, based on sample paired t-test between posttes score and follow up on experimental group it is founded that t = 0,850 with 0,408 significant, means that there is no difference. Thus it can be said that effect of treatment has stabilize characteristic. The conclusion acquired by this research is that problem solving learning has no influence to reduce the level of students' school stress.